Digitalisasi Sistem Penjualan pada Ubay Galon dengan Model Waterfall - Mohamad Fijar; Arista Prasetyo; Ahmad Syekar Azzami; Wasis Haryono (Jurnal Bisnis Inovatif dan Digital, 2025)
Manual transaction and stock recording at Ubay Galon causes various issues, such as data loss, record inaccuracies, and lack of real-time access. This study aims to design and develop a web-based sales information system to improve operational efficiency and data accuracy. The research was conducted at Ubay Galon, South Tangerang, using the Waterfall development method. Data collection techniques include observation, interviews, and literature studies. The system was designed using UML and implemented with web technologies. The result is a sales information system that records transactions, manages inventory, and generates automatic and real-time reports. The system also enhances data security with login and automatic backup features. In conclusion, the system effectively supports the digital transformation of Ubay Galon's business processes.